Prominent J-wave and T-wave alternans associated with mechanical alternans in a patient with takotsubo cardiomyopathy - Hojo, Rintaro (J Arrhythm, 2015)
A 74-year-old woman with takotsubo cardiomyopathy developed polymorphic ventricular tachycardia during the acute phase. She exhibited prominent J-wave and T-wave alternans preceding ventricular tachycardia. These abnormalities disappeared after recovery from myocardial stunning.